2001
DOI: 10.1038/nn0901-908
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor cell surface number and subunit stability are regulated by the ubiquitin-like protein Plic-1

Abstract: Controlling the number of functional gamma-aminobutyric acid A (GABA(A)) receptors in neuronal membranes is a crucial factor for the efficacy of inhibitory neurotransmission. Here we describe the direct interaction of GABA(A) receptors with the ubiquitin-like protein Plic-1. Furthermore, Plic-1 is enriched at inhibitory synapses and is associated with subsynaptic membranes. Functionally, Plic-1 facilitates GABA(A) receptor cell surface expression without affecting the rate of receptor internalization. Plic-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(212 citation statements)
references
References 43 publications
11
201
0
Order By: Relevance
“…For example, gephyrin and dystrophin have been shown to play a role in the anchoring of GABA A receptors, although no physical interaction with gephyrin has been demonstrated in vitro (39,40). GABARAP, a microtubuleassociated protein, and Plic-1, an ubiquitin-related protein, interact with GABA A receptor subunits and are involved in receptor trafficking (41,42). MAP1B is a large protein that binds actin and tubulin and is the only GABA C receptor binding partner identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…For example, gephyrin and dystrophin have been shown to play a role in the anchoring of GABA A receptors, although no physical interaction with gephyrin has been demonstrated in vitro (39,40). GABARAP, a microtubuleassociated protein, and Plic-1, an ubiquitin-related protein, interact with GABA A receptor subunits and are involved in receptor trafficking (41,42). MAP1B is a large protein that binds actin and tubulin and is the only GABA C receptor binding partner identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…Using the intracellular domain of the GABA A R ␤1 subunit (amino acids 303-425) we screened a rat hippocampal library in pPC86 as described (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…To identify proteins that regulate the endocytic sorting of GABA A Rs, we carried out a Y2H screen of a rat hippocampal library (15,16), with a bait encoding the intracellular domain of the GABA A R ␤1 subunit, and identified several interacting clones that encoded the central domain of rat HAP1 (residues 220-520). This protein exists as two C-terminal splice variants, HAP1a and HAP1b, with molecular masses of 75 and 85 kDa, respectively.…”
Section: Gabaar Endocytosis and Recycling In Neuronsmentioning
confidence: 99%
“…A glycine receptor has been shown to be internalized upon ubiquitination (Buttner et al 2001). A protein associated with GABA A receptors, Plic-1, indirectly controls the removal of GABA A through endocytosis (Bedford et al 2001). It was found that proteasome inhibitors prevent degradation of internalized GABA A receptors.…”
Section: Postsynaptic Roles Of the Uppmentioning
confidence: 99%